Indícios sincrônicos de gramaticalização: o uso do verbo chegar em orações coordenadas e na perífrase verbal [chegar (e) + v2]: contribuições para o ensino de gramática. - Macedo, Auricélia de (2010)
Based on North American Functional Linguistic Theory, our proposal is to describe and analyze the use of verb CHEGAR in verbal periphrasis such as [CHEGAR (E) + V2], where CHEGAR does not demonstrate a significance linked to physical movement. In linguistic literature, such periphrasis has been attributed several functions, related to aspectualization, emphasis of negative segments, and construction of mental spaces, among others. This study considers that the function of verb CHEGAR in the periphrasis in question is to indicate a global aspect, emphasizing a range of semantic-pragmatic nuances such as the sudden, instantaneous, or even abrupt character of the events refered to by the principal verb of the construction (V2), and/or the taking of initiative (sudden) by the agent (in the syntactic role of periphrastic subject), and/or subjective evaluations which go from surprise to frustration. Our objectives are the following: i) to describe and analyze the semanticpragmatic, morphosyntactic and social relationships which characterize the use of CHEGAR in verbal periphrases like [CHEGAR (E) + V2] and in coordinated/juxtaposed speech in which CHEGAR is the principal verb of the first utterance and is an elocution verb and the principal verb of the second; ii) identify, based on this description and analysis, synchrony proof in the grammaticalization of CHEGAR as an auxiliary verb in the periphrasis refered to. There was observed to be a strong similarity between coordinate/juxtaposed and periphrastic constructions. Such similarities strengthen the hypothesis that the use of CHEGAR as a lexical verb in coordinate/juxtaposed structures is the origin of the use of CHEGAR in the periphrastic structure, since the many properties encountered with higher frequency in lexical use are also just as frequently used as auxiliaries. Nevertheless, between the two constructions being studied, sufficient difference can be observed to see that CHEGAR, in the periphrasis [CHEGAR (E) V2], is behaving like an auxiliary verb, and shows typical properties of these types of verbs: i) in 100% of occurrences, it does not have a complement;ii) it has a co-referential subject in 100% of cases; iii) it does not appear with intervening material between it and V2. Besides this, CHEGAR, in periphrases, is predominant in nonneutral evaluation contexts, denoted by V2. Inspired by the results obtained, we propose strategies for the discussion of the [CHEGAR (E) V2] periphrases in both elementary and high schools.